Tracking Library for the Web - Melo, Eduardo Antonio Lundgren (2013)
In this dissertation, I designed and implemented a tracking library for the web aiming to provide a common infrastructure to develop applications and to accelerate the use of those techniques on the web in commercial products. It runs on native web browsers without requiring third-party plugins installation. This involves the use of several modern browser specifications as well as implementation of different computer vision algorithms and techniques into the browser environment. Between the several techniques available there are algorithms that can be used for different applications, such as, detect faces, identify objects and colors and track moving objects. The source language of the library is JavaScript that is the language interpreted by all modern browsers. The majority of interpreted languages have limited computational power when compared to compiled languages, such as C. The computational complexity involved in visual tracking requires highly optimized implementations. Some optimizations are discussed and implemented on this work in order to achieve good results when compared with similar implementations in compiled languages. A series of evaluation tests were made, to determine how effective these techniques were on the web.